Analisis Kualitatif Kandungan Formalin pada Tahu Putih di Pasar Tradisional Surakarta - Prasetyo, Berliani Ndaru; Hidayatullah, Muhammad Haqqi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Formalin is still frequently misused as a preservative in white tofu despite being prohibited in food products due to its toxic, irritant, and carcinogenic properties. Therefore, monitoring its presence in traditional markets requires detection methods that are simple, accurate, and well validated. Objective: This study aimed to detect formalin in white tofu sold in traditional markets in Surakarta City and to compare and validate three qualitative formalin detection methods (Nash reagent, KMnO₄, and Schiff reagent) in combination with Thin Layer Chromatography (TLC). Methods: A total of 10 white tofu samples were randomly collected from five traditional markets in Surakarta. The samples were extracted and analyzed using colorimetric tests with Nash, KMnO₄, and Schiff reagents, followed by confirmatory analysis using TLC. Method validation included determination of the limit of detection (LOD) and specificity. Results: Formalin was detected in 30% of the samples (B1, C1, and D2) by all applied methods, while the remaining 70% showed negative results. The LOD test indicated that the Nash reagent exhibited the highest sensitivity, detecting formalin at concentrations as low as 3.125 ppm, followed by TLC (6.25 ppm), Schiff reagent (25 ppm), and KMnO₄ (50 ppm). All methods demonstrated good specificity, with no false-positive results observed in blank samples and negative controls. Conclusion: This study confirms the misuse of formalin in 30% of white tofu samples from traditional markets in Surakarta. The Nash reagent is recommended as the most sensitive method for initial screening, while TLC serves as an effective confirmatory method. The combination of Nash reagent and TLC provides a simple, sensitive, and specific approach for formalin surveillance in white tofu at the field level.